The hepcidin-ferroportin axis controls the iron content of Salmonella-containing vacuoles in macrophages - Lim, Daejin; Marques, Oriana; Muckenthaler, Martina (Nature Communications, 2018)
The effects of iron on vacuole-resident Salmonella in macrophages are unclear. Here the authors show that the bacteria are not subject to nutritional inhibition by iron deprivation, but that iron depletion in the vacuole, via the hepcidin-ferroportin axis, inhibits the bactericidal effect of oxidative burst.
Gesehen am 20.02.2020